Catamenial Epilepsy: Discovery of an Extrasynaptic Molecular Mechanism for Targeted Therapy - Reddy, Doodipala Samba (Frontiers in Cellular Neuroscience, 2016)
Catamenial epilepsy is a complex neuroendocrine condition in which seizures are clustered around specific points in the menstrual cycle, most often around perimenstrual or periovulatory period. The pathophysiology of catamenial epilepsy still remains unclear, yet there are few animal models to study this gender-specific disorder. The pathophysiology of perimenstrual catamenial epilepsy involves the withdrawal of the progesterone-derived GABA-A receptor modulating neurosteroids as a result of the fall in progesterone at the time of menstruation. These manifestations can be faithfully reproduced in rodents by specific neuroendocrine manipulations. Because mice and rats, like humans, have ovarian cycles with circulating hormones, they appear to be suitable animal models for studies of perimenstrual seizures. Recently, we created specific experimental models to mimic perimenstrual seizures. Studies in rat and mouse models of catamenial epilepsy show enhanced susceptibility to seizures or increased seizure exacerbations following neurosteroid withdrawal. During such a seizure exacerbation period, there is a marked reduction in the antiseizure potency of commonly prescribed antiepileptics, such as benzodiazepines, but an increase in the anticonvulsant potency of exogenous neurosteroids. We discovered an extrasynaptic molecular mechanism of catamenial epilepsy. In essence, extrasynaptic delta-GABA-A receptors are upregulated during perimenstrual-like neuroendocrine milieu. Consequently, there is enhanced antiseizure efficacy of neurosteroids in catamenial models because delta-GABA-A receptors confer neurosteroid sensitivity and greater seizure protection. Molecular mechanisms such as these offer a strong rationale for the clinical development of a neurosteroid replacement therapy for catamenial epilepsy.